MEDIATING ROLE OF BRAND, COMMITMENT AND RISK ON THE RELATIONSHIP OF MOBILE BANKING SERVICE QUALITY AND MARKETING PERFORMANCE IN INDONESIA - Sutarso, Yudi; Sungkana, Bachtiar Eka Kaca; Anggriatama, Dendi Vio; Lavenia, Windi Mega (Universitas Brawijaya, Indonesia, 2021)
The purpose of this study is to investigate the mediating role of brand, commitment, and perceived risk on the relationship of mobile banking (MB) service quality and marketing performance (satisfaction and loyalty). A survey was conducted using a sample of 617 MB customers in Indonesia, i.e., Mobile BCA (BCA), BNI mobile (BNI), and Go mobile (CIMB Niaga). Structural equation modeling analysis was carried out with Warp PLS. The results show that MB service quality positively affects brand, commitment, satisfaction, and loyalty, while perceived risk has no effect. Another finding showed a relationship between brand image, commitment, and perceived risk on customer satisfaction and loyalty, although brand prestige does not affect loyalty. Thus, the partial mediating roles of brand image, commitment, and perceived risk are confirmed in the study. The findings will help academic researchers and bank practitioners understand MB customer attitude and behavior and help them in formulating strategies to manage the use of MB in Indonesia.